The influence of quality of services and hospital facilities on patient satisfaction: Case study at dr. Chasbullah Abdul Majid Hospital, Bekasi City - Ahmad Rafik; Nyoman Suardhita; Irwin Sukrisno Sugeng (Journal of Economics and Business Letters, 2021)
This study aims to determine how much influence the quality of hospital services and facilities have on patient satisfaction (a case study at dr. Chasbullah Abdul Majid Hospital, Bekasi city). The population in this study were outpatients at RSUD dr. Chasbullah Abdul Majid, Bekasi city. The sample in this study amounted to 100 patients, with the technique of determining the sample using nonprobability sampling and the sampling technique using accidental sampling, namely by looking for patients who happened to be having a doctor's examination. The results of data processing indicate the quality of hospital services and facilities and affect patient satisfaction, this is indicated by the account of service quality 4.714 with a significant level of 0.000 and t-count hospital facilities of 13.491 with a significant level of 0.000, the data above shows that the t-count value is greater than t table 1.660 and the significant value of both variables is below 0.05, then service and price have a very strong influence on patient satisfaction at RSUD dr. Chasbullah Abdul Majid Bekasi City which is shown by the coefficient of determination which shows the R2 value is 80.8%.